The IS/IT Strategy Planning Through Ward and Peppard Method in Automotive Spareparts Company - Suryana, Steven Immanuel; Fibriani, Charitas (PT Mattawang Mediatama Solution, 2024)
This research aims to develop an IS/IT strategy so that system implementation in carrying out the company's business processes becomes more effective and efficient. The method used in this research is the Ward and Peppard method, including analyses of Value Chain, SWOT, PEST, IS/IT Internal and External Environmental with McFarlan Strategic Grid, as well as System recommendations in the form of a framework and user interface of system recommendations based on Mc Farlan Strategic Grids implementation. The results of this research are several suggestions for developing existing systems, new frameworks if needed, as well as Users Interfaces from system recommendations. It is expected that this recommendation can be a solution for companies in overcoming the IS/IT related problems they face.